Phonological Development in Hearing Learners of a Sign Language: The Influence of Phonological Parameters, Sign Complexity, and Iconicity. Issue 3 (17th June 2015) - Ortega, Gerardo; Morgan, Gary
<x xml:space="preserve">Abstract</x> The present study implemented a sign‐repetition task at two points in time to hearing adult learners of British Sign Language and explored how each phonological parameter, sign complexity, and iconicity affected sign production over an 11‐week (22‐hour) instructional period. The results show that training improves articulation accuracy and that some sign components are produced more accurately than others: Handshape was the most difficult, followed by movement, then orientation, and finally location. Iconic signs were articulated less accurately than arbitrary signs because the direct sign‐referent mappings and perhaps their similarity with iconic co‐speech gestures prevented learners from focusing on the exact phonological structure of the sign. This study shows that multiple phonological features pose greater demand on the production of the parameters of signs and that iconicity interferes in the exact articulation of their constituents.